Analysis of the efficacy and factors affecting the prognosis of intracranial dissecting aneurysm treated with multi-stent overlap technique - Xiaolin Li; Huojun Hu; Lei Wang; Gao Yuan; Changtao Fu; Jinyang Ma; Quan Shao; Zhao Kang (BMC Neurology)
Abstract Objective The study aims to identify characteristics that impact the postoperative prognosis and recurrence of intracranial dissecting aneurysms (IDA) patients treated using multi-stent overlapping techniques. Methods Clinical data from 69 IDA patients treated with multistate-assisted spring coil embolization at the hospital between January 2017 and October 2023 were retrospectively reviewed, including clinical and imaging data gathered at admission and discharge. The prognosis was determined based on mRS grade at discharge, and the patients were divided into excellent prognosis (mRS 0–2 points) and poor prognosis (mRS 3–6 points). They were split into two groups: recurrence and no-recurrence, based on whether the patients had recurrence during surgical follow-up. The patient’s clinical information and aneurysm data were compared between the two groups to better understand the efficacy of multi-stenting for IDA and to investigate the factors that influence the good or negative prognosis of multi-stenting for IDA and recurrence. Results The prognosis was poor in 10 patients, 7 of whom died, while 59 had an excellent prognosis. Hunt-Hess classification (χ2 = 25.503a, P = < 0.01), hospitalization days (t=-3.873, P < 0.01), operation time (t=-1.970, P = 0.049), and aneurysm height (t=-1.969, P = 0.049) were all significant. 62 patients were discharged with 4 postoperative recurrences and 58 without recurrences in patients treated with multiple stents, with significant differences in the largest diameter (t=-2.235, P = 0.025), basal length (t=-2.149, P = 0.032), and position(located in pica base or not ) (χ2 = 10.955a, P = 0.001). The postoperative recurrence rate was 5.8%, but 85.8% reported satisfactory neurologic function (mRS ≤ 2). The case fatality rate was 10.1%. Conclusion Hunt-Hess grading on admission, aneurysm high, and operation time affect the prognosis of IDA, Hunt-Hess grade was an independent risk factor for prognosis. Aneurysm size, longest diameter, basal length, and location at the base of the pica affect recurrence. Located in pica base by the dissecting aneurysm is an independent risk factor for recurrence.